Changing pattern of infertility: A qualitative study - Rastogi, Sonam (South Asian Journal of Social Sciences and Humanities, 2025)
Infertility has a major concern for couples globally. It affects marital relationship, physical – psychological health, social status of infertile couples. It poses significant challenges of social norms, cultural beliefs, emotional well-being, physical, psycho-social pressure. This qualitative research paper explores changing pattern of infertility focusing on medical facilities, marital relationships, social pressure and its challenges. By throwing light on these changing patterns, this paper seeks to contribute to ongoing discourse surrounding infertility. Through in depth interview, this qualitative study aims to provide a comprehensive understanding of how perception, experience and stigma of infertility have changed over time. It also highlight, affect of advancement in Medical facilities, changes in marital relationship, changes in social pressure and ongoing stigma related to infertility.
Keywords: Marital relationship; societal perception; Assisted Reproductive Technology